And the killing goes on ; Patented drugs ; Anno XV Inno Sotto [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Focuses on Amnesty International and the continuing struggle of Filipino to stop violence. Debate rages on whether to junk the patent law or not. Fashion designer Inno Sotto presents his latest collection.